Farm Size, Capitalism, and Overuse of Agricultural Chemicals in China. Issue 3 (2nd July 2020) - Xu, Zhun
ABSTRACT: China's environment suffers from severe overuse of agricultural chemicals in recent decades. A popular opinion among policymakers and researchers is that land consolidation and larger farms will be instrumental in bringing down the consumption of fertilizer and improve the environment. By examining the relationship between farm size, capitalist production, and fertilizer intensity, we argue that larger and more capitalist farms in China do not necessarily have lower fertilizer intensity. I further argue that under capitalism a lower fertilizer intensity often induces an even higher level of fertilizer consumption. A substantial reduction in fertilizer consumption runs against the vested interest of capitalism. The problem of chemical overuse lies in the capitalist market economy which pushes both small and large farms to keep increasing fertilizer consumption. Only a society free from profit motive and exploitation can provide space for a truly sustainable and "rational" agriculture.